Analysis of Damage Detection Performance in a Concrete Structure using the Finite Element Method - Hrairi, Meftah (Journal of Advanced Research Design, 2025)
The field of civil engineering has been witnessing a significant technological revolution through the application of innovative ideas. One such idea gaining widespread attention is the utilization of smart materials for the health monitoring of structures. This study focuses on the feasibility of employing PZT (Lead-Zirconate-Titanate) patches on concrete buildings as a means of real-time health monitoring using an impedance-based technique. In this work, numerical analyses for damage identification in concrete structures that are both healthy and damaged are made. A finite element-based programme was used to model the beams of healthy and damaged concrete in the ANSYS commercial tool. Furthermore, parametric studies were done to determine the impedance signal in concrete structures with PZT. Based on the current results it has been found the Electromechanical Impedance (EMI) technique is useful to detect damage in healthy and damaged concrete structures.